The risk of acute coronary syndrome after retinal artery occlusion: a population-based cohort study. Issue 2 (21st August 2014) - Chang, Yuh-Shin; Chu, Chin-Chen; Weng, Shih-Feng; Chang, Chun; Wang, Jhi-Joung; Jan, Ren-Long
Abstract : Aim: To investigate the risk of acute coronary syndrome (ACS) following retinal artery occlusion (RAO). Methods: The study cohort included all patients diagnosed with RAO between January 1999 and December 2008 (n=688) in the Taiwan Longitudinal Health Insurance Database 2000. The control group included randomly selected patients (n=4128) from the same database that were matched to the study group, using a propensity score, for age, gender, and comorbid diabetes mellitus, hypertension, hyperlipidaemia, chronic renal disease and atrial fibrillation status. The ACS-free survival rate was calculated using Kaplan–Meier analysis. Cox proportional hazard regression analysis was used to obtain the adjusted HR for ACS after adjustment for potential confounding factors. The incidence and risk of ACS were compared between the RAO and control groups. Results: Thirty-seven patients in the RAO group (5.38%) and 138 controls (3.34%) had ACS (p=0.0063) during the follow-up period, resulting in a significantly higher risk of ACS in the RAO group (HR=1.67, 95% CI 1.16 to 2.40). After adjustment for potential confounders, the HR for developing ACS in the RAO group was 1.72 (95% CI 1.20 to 2.47) times higher than that of controls. When stratified by RAO type, the adjusted HR for ACS was 3.57 (95% CI 2.09 to 6.10) for the central RAO subgroup. Conclusions: We found that RAO increased the risk for ACS. We recommend thorough follow-up cardiovascular examinations and medical prevention for ACS in patients following RAO.